2021
DOI: 10.1101/2021.05.18.444724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering ion transport and ATPase coupling in the intersubunit tunnel of KdpFABC

Abstract: KdpFABC, a high-affinity K+ pump, combines the ion channel KdpA and the P-type ATPase KdpB to secure survival at K+ limitation. Here, we apply a combination of cryo-EM, biochemical assays, and MD simulations to illuminate the mechanisms underlying transport and the coupling to ATP hydrolysis. We unambiguously show that ions are transported via an intersubunit tunnel through KdpA and KdpB. At the subunit interface, the tunnel is constricted by a phenylalanine, which, by polarized cation-π stacking, controls K+ … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 86 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…Thorough exploration of the surrounding membrane environment requires simulation timescales that are sufficient to sample multiple lipid binding/unbinding events across the TMD 14,18 . This is readily enabled through use of coarse-grained (CG) and atomistic simulations which have been used to successfully predict lipid binding sites subsequently validated via experimental structural and biophysical methods 1921 . Thus, there is a clear complementarity between MD simulations and structure determination by cryo-EM for identification and characterisation of protein-lipid interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Thorough exploration of the surrounding membrane environment requires simulation timescales that are sufficient to sample multiple lipid binding/unbinding events across the TMD 14,18 . This is readily enabled through use of coarse-grained (CG) and atomistic simulations which have been used to successfully predict lipid binding sites subsequently validated via experimental structural and biophysical methods 1921 . Thus, there is a clear complementarity between MD simulations and structure determination by cryo-EM for identification and characterisation of protein-lipid interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Energetically significant aromatic interactions involving phenylalanine are believed to be widespread in nature [12,13]. Based on emerging structural data, they have been increasingly proposed to play important mechanistic roles in ligand recognition [14][15][16][17][18][19], and protein-protein interactions, both in normal function [20,21] and as a result of clinical mutation [22]. They may also play important roles in membrane anchoring, via attraction of the benzyl side chain to choline lipid headgroups [23], and have recently been proposed to mediate conduction in some ion channels [24].…”
Section: Introductionmentioning
confidence: 99%
“…When the external K + is limited (<100 µM) and Trk fails to take up potassium, the high-affinity potassium uptake system Kdp is produced and ensures the accumulation of K + with a moderate uptake rate (100-150 µmol*g -1 *min -1 ) fuelled by ATP hydrolysis. Kdp is a primary active K + pump and consists of the four subunits KdpF, KdpA, KdpB and KdpC, which allows K + uptake by the combination of two half-channels formed by the K + channel-like subunit KdpA, which as well belongs to the SKT family, and the P-type ATPase KdpB (Silberberg et al, 2021;Stock et al, 2018). Under acidic pH, the secondary active K + /H + symporter Kup has a particular high activity and exhibits K + translocation with similar rates to that of Trk but shows a slightly increased affinity towards K + (0.5 mM).…”
Section: Variety Of Bacterial Potassium Translocation Systems Fulfil ...mentioning
confidence: 99%
“…In addition to these general effects of membrane physiology, the phospholipid CL has been described to play a regulatory role as a specific ligand for several membrane proteins in E. coli, including the ammonium transporter AmtB, the translocon SecYEG or the leucine transporter LeuT (Corey et al, 2018;Gupta et al, 2017;Patrick et al, 2018). Recently, it was also shown that CL binds to the potassium transporter KdpFABC from E. coli with high-affinity, stimulating ATPase activity (Silberberg et al, 2021). More generally, binding sites for CL in the TM domains of these proteins were described to be characterised by following features: Several basic residues are located in close proximity, a glycine residue is present in the same plane as well as aromatic amino acids like phenylalanine .…”
Section: Interaction Of Ktrb's N Terminus With the Membranementioning
confidence: 99%